FİRDEVSÎ-İ RÛMÎ’NİN SÜLEYMÂNNÂME-İ KEBÎR’İNDEKİ DEYİMLER - (:unkn) unknown (My University, 2014)
Bu makalede XV. yüzyıl sonu XVI. yüzyıl başlarında yaşamış olan Firdevsî (Firdevsî-i Rûmî, Firdevsî-i Tavîl, Uzun Firdevsî)'nin kısaca hayatı ve eserleri hakkında bilgi verilmiş ve Süleymânnâme'nin 43. cildindeki deyimler incelenmiştir. Eski Anadolu Türkçesi Dönemi'nde eserlerini veren Firdevsî, Fatih Sultan Mehmed, Sultan II. Bayezid ve Yavuz Sultan Selim zamanında yaşamıştır. Süleymânnâme-i Kebîr XVI. yüzyılın başlarında Firdevsî-i Rûmî tarafından yazılmış olup Süleyman Peygamber'in hayatını ve menkıbelerini anlatan ansiklopedik mahiyette bir eserdir. Süleymânnâme'de Hazreti Süleyman kahramanlarından olan Alp Er Tunga olduğu ifade edilir. Eser ayrıca doğu mitolojisi, diğer peygamber kıssaları, tarih, hikmet, hendese, nücum, coğrafya ve tıbba ait çeşitli konuları içerir. Süleymânnâme'de anlatımın sade, ilgi çekici ve canlı üslubu, Dede Korkut Hikâyeleri ile paralellik taşıdığı noktasında dikkat çekmektedir. Eserlerindeki akıcılığı sahip olduğu zengin söz varlığı sağlamaktadır. Süleymânnâme-i Kebîr'de yer alan atasözleri, deyimler, ikilemeler ve ayrıca ses ve söz tekrarları ile oluşmuş söz birliklerinin, kültürel açıdan Türkiye Türkçesine katkısı önemlidir. Süleymânnâme'nin incelenen 43. cildinde yer alan çok sayıdaki deyim; dil açısından Eski Anadolu Türkçesi özelliklerini ve dönemine ait değer yargılarını ifade eden kalıp yapılar hakkında bilgi sahibi olmamızı sağlarken günümüze ait kalıplaşmış ifadeler olan deyimler konusunda kıyaslama imkânı da vermektedir. Süleymânnâme'deki deyimlerden bir kısmı aynen günümüzde kullanılmakta, bir kısmı ses veya anlam değişimine uğramış, bazıları da artık kullanılmamaktadır

This article gives a brief information about the life and the works of Firdevsi (Firdevsi-i Rumi Firdevsi-i Tavil) who has lived within the ends of the 15th till the beginnings of the 16th century and the idioms found in Süleymanname’s 43th volume have been reviewed. Firdevsi, who has completed his works within the time of the Old Anatolian Turkish, has lived during the reigns of Fatih Sultan Mehmed, Sultan Bayezid II and Sultan Selim I. Süleymanname-i Kebir was written by Firdevsi-i Rumi at the beginning of 16th century as a work of an encyclopedic nature narrating the life and tales of Prophet Soliman. In addition, this work features topics about eastern mythologies, tales of other prophets, history, wisdom, geometry, astronomy, geography and medicine. It is stated in Süleymanname that Efrasiyab-ı Türk who struggled against Prophet Solomon was actually Alp Er Tunga one of the figures of the Turkish mythology. The author uses such a plain, interesting and lively fashion of expression in this work to the point that it draws attention to the parallelism it has with Dede Korkut stories. His rich use of vocabulary facilitates the fluency in his works. Proverbs, idioms, hendiadyoins and also word unities formed by sound and word repetitions which take place in Süleymanname-i Kebir have a significant cultural contribution to the Turkish language of Turkey. Many of the idioms which take place in Süleymanname’s reviewed 43rd volume not only enable us to have some idea about the linguistic characteristics of the Old Anatolian Turkish and the stereotyped structures which express the value pronouncements of that period but also provide us with the possibility of making comparisons regarding the contemporary idioms. Some of the idioms in Süleymanname are being used at the present day in the original form while others have went through sound or meaning alternation and some of them are not being used any longer
IDIOMS IN SÜLEYMANNAME-I KEBIR’S FIRDEVSI-I RUMI